2015
DOI: 10.1002/cssc.201500580
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Metal–Organic Frameworks for Enhanced Stability under Humid Carbon Dioxide Capture Conditions

Abstract: Metal-organic frameworks (MOFs) have been highlighted recently as promising materials for CO2 capture. However, in practical CO2 capture processes, such as capture from flue gas or ambient air, the adsorption properties of MOFs tend to be harmed by the presence of moisture possibly because of the hydrophilic nature of the coordinatively unsaturated sites (CUSs) within their framework. In this work, the CUSs of the MOF framework are functionalized with amine-containing molecules to prevent structural degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…However, the reported MOFs usually have unsatisfactory CO 2 capture capacity. In addition, it is also necessary to examine the stability and performance of MOFs in humid conditions for the practical use . For example, some amine‐functionalized MOFs, with excellent CO 2 capture ability, is very hydrophilic and can adsorb considerable amount of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported MOFs usually have unsatisfactory CO 2 capture capacity. In addition, it is also necessary to examine the stability and performance of MOFs in humid conditions for the practical use . For example, some amine‐functionalized MOFs, with excellent CO 2 capture ability, is very hydrophilic and can adsorb considerable amount of water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The use of steam for CO2 recovery has been proposed as a cost-effective strategy for amine-functionalized adsorbents (17)(18)(19)(20)(21)(22), particularly because low-grade steam is inexpensive and readily available in most industrial processes. Unfortunately, engineering adsorbents with stability in the presence of steam is an ongoing issue (19,(23)(24)(25).…”
mentioning
confidence: 99%
“…Ethylenediamine (EDA) molecules, on the other hand, have low-molecular weight, relatively high vapour pressure (∼10 Torr, 20 °C) at ambient condition and contain terminal amine groups in EDA molecules, which are known to interact more strongly with a variety of MOFs, particularly those with open or unsaturated metal sites (for example, found in MOF-74) by forming metal-amine complexes121314. Moreover, previous studies have shown that EDA molecules cannot easily penetrate into MOFs due to their size and strong interaction with the framework, requiring refluxing in solution (for example, anhydrous toluene)121516. For instance, in Mg-MOF-74, that is, Mg 2 (dobdc) with dobdc=2,5-dihydroxybenzene dicarboxylic acid, the best attempts only lead to ∼0.13 EDA per Mg 2+ metal centre, which is an order of magnitude less than theoretically possible1216.…”
mentioning
confidence: 99%
“…Moreover, previous studies have shown that EDA molecules cannot easily penetrate into MOFs due to their size and strong interaction with the framework, requiring refluxing in solution (for example, anhydrous toluene)121516. For instance, in Mg-MOF-74, that is, Mg 2 (dobdc) with dobdc=2,5-dihydroxybenzene dicarboxylic acid, the best attempts only lead to ∼0.13 EDA per Mg 2+ metal centre, which is an order of magnitude less than theoretically possible1216. The difficulty to fully load EDA in MOF-74 highlighted by these pioneering studies suggests that, without extensive refluxing, EDA molecules should only adsorb on the surface of MOF crystals.…”
mentioning
confidence: 99%